EFEKTIVITAS PENGGUNAAN MEDIA PUZZLE BERBASIS MAKE A MATCH UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR LOGIS - Arimbi Hariba Cemerlang, Dipta; Nurdyansyah, Nurdyansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to develop a puzzle media that can facilitate students in receiving material delivered by teachers and make learning more interesting, enjoyable, and free from boredom. The existence of this puzzle media will increase students' learning interest. Furthermore, it is also to determine the feasibility and effectiveness of the development results of make a match-based puzzle media. This research uses the Research and Development (R&D) method. The research model uses ADDIE, namely analysis, design, development, implementation, and evaluation. The data collection technique used is questionnaires and tests in the form of descriptive quantitative data. The media to be used for learning is considered valid by three experts as evidenced by the results: (1) material experts have a validity percentage of 85%, (2) media experts 80%, and (3) language experts 88%. After declared valid, the media was tested on fourth-grade students at MI Al Hidayah. Based on the results of the t-test analysis on the pre-test average score of 65.6 and post-test 86.9. Because the sig. value (2-tailed) or test 1 is 0.00, which means ≤ 0.05, it can be concluded that Ho is rejected and Ha is accepted. The conclusion drawn from this research shows that there is a significant influence of puzzle media on the logical thinking of fourth-grade students at MI Al Hidayah.